A silicon nitride ISFET based immunosensor for Ag85B detection of tuberculosis. Issue 20 (3rd August 2016) - Saengdee, Pawasuth; Chaisriratanakul, Woraphan; Bunjongpru, Win; Sripumkhai, Witsaroot; Srisuwan, Awirut; Hruanun, Charndet; Poyai, Amporn; Phunpae, Ponrut; Pata, Supansa; Jeamsaksiri, Wutthinan; Kasinreak, Watchara; Promptmas, Chamras
Abstract : An ISFET-based sensor was developed for Ag85B detection by immobilization of anti-Ag85B. The precision (CV%) and accuracy of this sensor were 9.73–10.99% and 95.29%, respectively. Abstract : A silicon nitride Ion Sensitive Field Effect Transistor (ISFET) based immunosensor was developed as a low-cost and label-free electrical detection for the detection of antigen 85 complex B (Ag85B). The sensing membrane of the ISFET was modified with 3-aminopropyltriethoxysilane (APTES) followed by glutaraldehyde (GA), yielding an aldehyde-terminated surface. This group is available for immobilization of a monoclonal antibody against a recombinant Ag85B protein (anti-Ag85B antibody). The optimal concentration for anti-Ag85B antibody immobilization onto the modified ISFET was 100 μg ml −1 . This optimal condition provided the maximal binding capability and minimal non-specific background signal. The binding event between the recombinant Ag85B antigen and anti-Ag85B antibody on the ISFET surface is presented by monitoring the gate potential change at a constant drain current. The dose response for the recombinant Ag85B protein showed a linear response between 0.12 and 1 μg ml −1 without significant interference from other recombinant proteins. The analytical imprecision (CV%) and accuracy of this Ag85B protein biosensor were 9.73–10.99% and 95.29%, respectively. In addition, an irrelevant antibody and other recombinant proteins were employed as a negative control to demonstrate the non-specific interaction of the antigen and antibody. The success of this immunosensor system for Ag85B protein detection facilitates the construction of a promising device which can shorten the turnaround time for the diagnosis of tuberculosis compared to a standard culture method. Furthermore, this device could also be applied for real-time growth monitoring of Mycobacterium tuberculosis in a mycobacterial culture system.